Acute chagas disease: new global challenges for an old neglected disease. - Daniela V Andrade; Kenneth J Gollob; Walderez O Dutra (Public Library of Science (PLoS), 2014)
Chagas disease is caused by infection with the protozoan Trypanosoma cruzi, and although over 100 years have passed since the discovery of Chagas disease, it still presents an increasing problem for global public health. A plethora of information concerning the chronic phase of human Chagas disease, particularly the severe cardiac form, is available in the literature. However, information concerning events during the acute phase of the disease is scarce. In this review, we will discuss (1) the current status of acute Chagas disease cases globally, (2) the immunological findings related to the acute phase and their possible influence in disease outcome, and (3) reactivation of Chagas disease in immunocompromised individuals, a key point for transplantation and HIV infection management.